2011
DOI: 10.1073/pnas.1109859108
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of pancreatic islet β-cell mass using a second-generation fluorescent exendin-4 analog

Abstract: The hallmark of type 1 diabetes is autoimmune destruction of the insulin-producing β-cells of the pancreatic islets. Autoimmune diabetes has been difficult to study or treat because it is not usually diagnosed until substantial β-cell loss has already occurred. Imaging agents that permit noninvasive visualization of changes in β-cell mass remain a high-priority goal. We report on the development and testing of a near-infrared fluorescent β-cell imaging agent. Based on the amino acid sequence of exendin-4, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 38 publications
9
127
0
3
Order By: Relevance
“…This is probably due to the fact that the antagonist exendin- is not suitable for in vivo targeting of the GLP-1R [31], indicating that agonistic activity is required for successful visualisation of beta cells in vivo. Importantly, Reiner et al have recently demonstrated the in vivo targeting of beta cells with a fluorescent labelled exendin-4 analogue [32].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that the antagonist exendin- is not suitable for in vivo targeting of the GLP-1R [31], indicating that agonistic activity is required for successful visualisation of beta cells in vivo. Importantly, Reiner et al have recently demonstrated the in vivo targeting of beta cells with a fluorescent labelled exendin-4 analogue [32].…”
Section: Discussionmentioning
confidence: 99%
“…7,8,20 In the db/db time study a weightadjusted dose of 804 mg/kg (160 nmol/kg) was used. Vehicle controls were injected with 200 ml 1 X DPBS.…”
Section: Probing Of Mice and Preparation For Histologymentioning
confidence: 99%
“…Due to these properties, exendin-4-based imaging probes have been explored for in vivo imaging of b cells and insulinomas in several imaging modalities. [7][8][9][10][11][12][13] Although GLP-1R agonists are well studied for their pharmacological effects on b cells, less is known concerning the specificity and dynamics of GLP-1R expression in the pancreas. This is mainly due to a lack of specific antibodies against the GLP-1R, and species differences in GLP-1R expression.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative imaging of insulinomas is critical, because it helps to precisely localize these often very small lesions in the pancreas. Therefore, imaging probes for optical (2), bimodal (3), SPECT (4-7), and PET (8-13) imaging as well as MRI (14) were developed to localize GLP-1 receptors preoperatively and in addition to determine b-cell mass in diabetic animal models and potentially in patients. In particular, SPECT (4,5,7) and PET (8,13,15) agents were successfully translated into the clinic, and several promising clinical studies were reported.…”
mentioning
confidence: 99%